Construction of Pakistan Army in the Western Media: Discourse Analysis of Leading Articles of Time and The Economist - Zafar Iqbal and Zareen Zubair (Journal of Political Studies, 2014)
Media do not present, but represent and construct images by framing people and events in a way that may or may not be based on realities. This is merely done following the agenda set by the bodies influencing the media and its policies. After 9/11, Pakistan has given the US full support to counter terrorism. Various operations were carried out by the Pakistan Army in order to fight off terrorism, which resulted in heavy loss of military lives. Yet it was a common notion that the US media did not support Pakistan or its Army in its contents. The aim of this study was to see as how Pakistan’s Army was constructed in the Western media -Time (US) and The Economist (UK). The articles were retrieved using Lexis Nexis from April 2010 to April 2012. The discourse analyses were carried using corpus modus to understand the underlying meanings. Analyses from both newsmagazines were then compared.